Fuzzy Based Design for Third-Party Pipeline Failures in the Niger Delta Region of Nigeria - GO Ariavie; RE Emetitiri; OE Ononeme; ID Olowu (Journal of Applied Sciences and Environmental Management)
A Fuzzy based design for assessing failures of pipelines occasioned by third party in the Niger Delta Region of Nigeria has been proposed in this study. Twelve factors earlier identified by Ariavie et al (2010), were further grouped into four, viz : violence, desperation, misconduct and agricultural categories to allow for a less tedious rule base development. Each category has inputs (base inputs) plugged into it which is in turn plugged into another system (main engine). Based on this, the fuzzy model was designed, using MATLAB fuzzy toolbox to develop a hypothetical simulation which simply involves the feeding of randomly generated values between 0 and 1 to the controllers. The evaluation process of the first expert is presented and obtained for the four categories Risk values as 0.533, 0.509, 0.442 and 0.552 for violence, desperation, misconduct and agricultural respectively, with total risk value being 0.063.